Quality assessment of shoe leather based on the properties of strength and comfort, collected from different footwear and leather industries in Bangladesh - Hossain, Md. Delwar (Array, 2020)
Based on the environmental condition, a shoe manufactured with different suitable materials has to provide optimum comfort and strength features by using high-quality leather parts. The aim of the study is to evaluate the quality of the shoe upper leather in Bangladesh. Ten different types of shoe leather, made from cow hides and goat skins, were collected from different footwear and leather industries in Bangladesh. The research was carried out by using approved methods of analysis as per the International Union of the Society of Leather Technologists and Chemists" official methods for physical and chemical analysis. Physical and chemical properties, which were studied three times for each of the samples, were tensile strength, percentage of elongation, tearing strength, grain crack resistance, water vapor permeability, flexing endurance, scuff resistance, perspiration fastness, color rub fastness, bond strength of the finish film, the pH, moisture content, chromic oxide content and fat content, respectively. From the study, it has been revealed that samples 02 and 08 were completely unacceptable, samples 04, 05 and 07 were moderately acceptable, and the remaining samples, 01, 03, 06, 09 and 10, were strongly acceptable on the basis of the ISO standard for shoe leather. To get the better quality, the above mentioned tests should be improved, thus the demand and the value of shoe leather, as well as footwear, will be increased and the rejection rate will be decreased gradually.